2020
DOI: 10.1002/cssc.202001310
|View full text |Cite
|
Sign up to set email alerts
|

Induced CO2 Electroreduction to Formic Acid on Metal−Organic Frameworks via Node Doping

Abstract: Metal−organic frameworks (MOFs), combining the advantages of heterogeneous and homogeneous components, have been explored as catalytic materials for the CO2 electroreduction reaction (CO2ERR). However, the unmatched metal nodes result in MOFs having lower faradaic efficiencies (FEs) and limited current densities in CO2ERR. Herein, we report a general strategy to promote activities of MOFs via node doping in CO2ERR. With ion exchange, an active tin node was doped into zeolitic imidazolate framework‐8 (ZIF‐8) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Geng and collaborators utilize node metal ion exchange strategy to prepare an Sn-doped ZIF-8 (Geng et al, 2020). The doping method is also a good method for introducing two metals at the same time.…”
Section: Metal Node Stabilization Strategymentioning
confidence: 99%
“…Geng and collaborators utilize node metal ion exchange strategy to prepare an Sn-doped ZIF-8 (Geng et al, 2020). The doping method is also a good method for introducing two metals at the same time.…”
Section: Metal Node Stabilization Strategymentioning
confidence: 99%
“…3, although the Cu HF electrode itself shows some electrochemical active for gas-phase CO 2 reduction to multicarbon products, the current density and their faradaic efficiencies are much lower compared to the Sn-modified electrodes. Introducing Sn species into aqueous CO 2 electroreduction usually promote the formation of HCOOH [24][25][26][27][28] , while during gas-phase CO 2 electroreduction, SnO 2 nanoparticles on Cu surface play more important roles. The HCOOH species facilitated by virtue of SnO 2 are further converted into *CHO intermediate at the SnO 2 /Cu interfacial, which subsequently dimerize into C2 intermediate glyoxal (CHO) 2 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…27 Geng et al found the Sn 2+ node in ZIF-8 can accelerate the HCOOH formation with a FE of 74 % and a total current density of 27 mA cm -2 . 28 These findings witnessed the great promotion of HCOOH formation by introducing of Sn species in aqueous CO 2 electroreduction. However, during gas-phase CO 2 electroreduction, SnO 2 nanoparticles on HF surface would play more important roles beyond facilitating to produce HCOOH species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…52 In a previous report, ZIF-8 was employed in the CO 2 electroreduction reaction by FDH and played an important role in increasing the CO 2 dissolvability. 53 There is also information on the application of ZIF-8 in living cells. The addition of ZIF-8 promoted CO 2 reduction by 72.9% compared to the condition without ZIF-8 by Arthrospira platensis cells.…”
Section: Role Of Hcomentioning
confidence: 99%